Resveratrol loaded cubic phase nanoparticles with enhanced oral bioavailability - Rawat, Neeraj Kumar; Torris, Arun; Bhat, Suresh; Mahadik, Kakasaheb; Patil, Sharvil (BioNanoScience, 2021)
Resveratrol (RES), a naturally occurring hydrophobic polyphenolic compound, has shown potential anticancer activity. However, due to low aqueous solubility and extensive first pass metabolism (primarily by cytochrome enzymes), it shows poor oral bioavailability. In the present work, novel RES loaded cubosomes of glycerol monooleate (GMO) and Gelucire 44/14 (GL44) (RES-Cubs) were prepared. RES-Cubs were prepared by emulsion evaporation technique and optimized using 32 factorial design. The optimized RES-Cubs were assessed for particle size, zeta potential, entrapment efficiency, FTIR, TEM, SAXS, in vitro resveratrol release and oral bioavailability. RES-Cubs showed an average particle size of 121.7 ± 2.54 nm with adequate entrapment efficiency of about 82.0 ± 2.35% w/w. The analysis of SAXS profile of RES-Cubs revealed Pn3m crystallographic space group containing diamond cubic phase. In vitro RES release profile of RES-Cubs exhibited markedly sustained release of resveratrol. Furthermore, RES-Cubs demonstrated considerable enhancement in oral bioavailability (ninefold) of resveratrol as compared to RES alone. The developed RES loaded cubosomes bearing cytochrome enzyme inhibitor property can act as promising nanocarrier in the delivery of lipophilic drugs with a drawback of in vivo degradation by cytochrome enzymes.

Rivaroxaban eutectics with improved solubility, dissolution rates, bioavailability and stability - Shaligram, Parth S.; George, Christy P.; Sharma, Himanshu; Mahadik, Kakasaheb R.; Patil, Sharvil; Vanka, Kumar; Arulmozhi, S.; Gonnade, Rajesh G. (Crystengcomm, 2023)
Rivaroxaban (RXB) is a direct factor Xa inhibitor used for the treatment of deep vein thrombosis (DVT, a blood clot in the leg) and pulmonary embolism (PE, a blood clot in the lung) and to prevent blood clots in atrial fibrillation following hip or knee surgery. However, RXB suffers from poor solubility that hinders its broader application. Although its cocrystals are reported for solubility enhancement, the methodology used to prepare multi-component crystals is complex. Also, it uses hazardous solvents to develop cocrystals. We have prepared eutectics of RXB with caffeic acid (CAA), coumaric acid (CA), fumaric acid (FA), succinic acid (SA), mandelic acid (MA) and trimesic acid (TA) and analyzed them using hot stage microscopy (HSM), differential scanning calorimetry (DSC), powder X-ray diffraction (PXRD), and fourier transform infrared spectroscopy (FTIR) techniques. The saturation solubility and dissolution rate profiles were also obtained to investigate the effect of eutectics on these parameters. Amongst all the coformers tested, coformers CAA, CA, and FA showed significant enhancement in the solubility of RXB. The powder dissolution rate of the eutectics showed considerable enhancement compared to that of RXB. In vivo pharmacokinetic study was carried out for RXB-CAA, RXB-CA and RXB-FA in rats and compared with RXB, which showed 1.5 and 1.4 times enhancement in relative bioavailability for RXB-CAA and RXB-CA, respectively. Stability studies were carried out as per ICH guidelines for all the eutectics, which revealed excellent stability over six months under accelerated (40 degrees C and 75%) conditions and twelve months under long-term (30 degrees C and 60% RH) conditions. The DFT studies carried out using the B3LYP/TZVP level of theory revealed higher Gibbs free interaction energy (Delta G(int)) for homosynthons (drugMIDLINE HORIZONTAL ELLIPSISdrug and coformerMIDLINE HORIZONTAL ELLIPSIScoformer) than heterosynthons (drugMIDLINE HORIZONTAL ELLIPSIScoformer).